2010
DOI: 10.3390/s101210896
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Depth of Anaesthesia

Abstract: One of the current challenges in medicine is monitoring the patients’ depth of general anaesthesia (DGA). Accurate assessment of the depth of anaesthesia contributes to tailoring drug administration to the individual patient, thus preventing awareness or excessive anaesthetic depth and improving patients’ outcomes. In the past decade, there has been a significant increase in the number of studies on the development, comparison and validation of commercial devices that estimate the DGA by analyzing electrical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 182 publications
(236 reference statements)
1
84
0
Order By: Relevance
“…These include the Bispectral Index (BIS TM ) monitor, the Narcotrend TM monitor, Cerebral state monitor (CSM TM ) and M-entropy TM module [78]. Generally, these monitors were developed by searching for a computational parameter capable of relating changes in the EEG signal characteristics to the druginduced changes during anaesthesia [50].…”
Section: Controlled Variablesmentioning
confidence: 99%
“…These include the Bispectral Index (BIS TM ) monitor, the Narcotrend TM monitor, Cerebral state monitor (CSM TM ) and M-entropy TM module [78]. Generally, these monitors were developed by searching for a computational parameter capable of relating changes in the EEG signal characteristics to the druginduced changes during anaesthesia [50].…”
Section: Controlled Variablesmentioning
confidence: 99%
“…No 'ideal' depth of anaesthesia monitor exists and it is perhaps troubling that most anaesthetists spend their working lives administering titrated drugs with no target organ monitoring. The various techniques and technologies available include the isolated forearm technique, and both electroencephalograph-derived and auditory evoked potential-derived signals; these have been reviewed previously [198]. Their effectiveness and role in preventing awareness are controversial and affected by the anaesthetic technique or agents employed.…”
Section: Maintenance Of Anaesthesia and Awarenessmentioning
confidence: 99%
“…BIS) or AEP based anaesthesia monitoring devices are not able to reliably assess the patient's depth of anaesthesia when ketamine, xenon or nitrous oxide are used', and 'the effects of nitrous oxide on the raw EEG or on the BIS value are varied and therefore unpredictable'. 2 Furthermore, Ibrahim et al found 'Individual BIS scores demonstrate significant variability, making it difficult to predict sedation depth. BIS was a better predictor of propofol sedation than sevoflurane or midazolam'.…”
Section: Moderate Sedation In Paediatric Dental Patientsmentioning
confidence: 99%
“…The term 'moderate sedation' is the new term for 'conscious sedation'. The Guideline for Monitoring and Management of Pediatric Patients During and After Sedation for Diagnostic and Therapeutic Procedures, 2 which was developed and endorsed by the American Academy of Pediatrics and the American Academy of Pediatric Dentistry (adopted 2006) reads as follows: 'Moderate sedation' (old terminology 'conscious sedation' or 'sedation/analgesia'): a druginduced depression of consciousness during which patients respond purposefully to verbal commands (e.g. 'open your eyes' either alone or accompanied by light tactile stimulation -a light tap on the shoulder or face, not a sternal rub).…”
Section: Moderate Sedation In Paediatric Dental Patients: Author's Replymentioning
confidence: 99%